2020
DOI: 10.12659/msm.925877
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Infection Control Behaviors to Prevent COVID-19: An Online Survey of Nursing Students in Anhui, China in March and April 2020

Abstract: Background The pandemic of coronavirus disease 2019 (COVID-19) has become a major public health challenge all over the world. People’s knowledge, attitudes, and preventive behaviors about diseases affect the degree of adherence to control measures. This study aimed to survey the affecting factors of COVID-19 prevention behavior among nursing students in China. Material/Methods Six-hundred thirteen nursing students in Anhui, China participated in an online survey from Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 23 publications
9
27
0
2
Order By: Relevance
“…The result of multiple regression analysis of the factors affecting such behaviors indicated that a high level of e-HL led to a high adherence to infection-preventive behaviors. This is consistent with a study on undergraduate students where e-HL correlated with getting vaccinations, and a study conducted in China on nursing students where e-HL correlated with COVID-19 infection-control behaviors [ 28 , 29 ]. e-HL indicates the ability to use the Internet to search, understand, and apply the necessary healthcare information with respect to health-related behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…The result of multiple regression analysis of the factors affecting such behaviors indicated that a high level of e-HL led to a high adherence to infection-preventive behaviors. This is consistent with a study on undergraduate students where e-HL correlated with getting vaccinations, and a study conducted in China on nursing students where e-HL correlated with COVID-19 infection-control behaviors [ 28 , 29 ]. e-HL indicates the ability to use the Internet to search, understand, and apply the necessary healthcare information with respect to health-related behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were reported from students at the University of Sharjah 12 and nursing students in China (100% and 91.2%, respectively). 28 It is important that people be informed about common symptoms of COVID-19, via valid sources to prevent misconceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies emphasized the importance of eHealth literacy during COVID-19 [ 19 , 20 ]—and in the research of netizens [ 21 ], health care workers [ 22 ], and nursing students [ 23 ] it was found that eHealth literacy was related to COVID-19 prevention behavior—few studies have focused on the relationship between eHealth literacy and other COVID-19–related health behaviors other than preventive behaviors, especially among college students. Conventional health behaviors, such as physical exercise and nutritious eating, are also COVID-19–related health behaviors.…”
Section: Introductionmentioning
confidence: 99%